Continuity or Change? Disability Policy and the Rudd Government - Soldatic, Karen; Pini, Barbara (Cambridge University Press, 2012)
This article reports on shifts and continuities in policy relating to disabled people and theadministrative apparatus of federal disability policy under the Rudd government (2007–10). It begins with a brief historical overview of disability policy in Australia. It then givesparticular attention to highlighting the contentious and dramatic changes to disabilitypolicy which were instigated by the Howard government (1996–2007). Following this,attention is focused on the major developments in disability policy and administrationwith the election of the Rudd Labor government in 2007. Through this discussion, wedemonstrate the ways the altered vocabularies, practices and instruments of the state havemanifested in relation to disability policy in Australia, ultimately shaping opportunities foreither inclusion or exclusion at the national level among disabled people.